Thermo-mechanical fatigue testing and simulation using a viscoplasticity model for a P91 steel - Hyde, Christopher J.; Sun, W.; Hyde, T.H.; Saad, A.A. (Elsevier, 2012)
An experimental programme of cyclic thermo-mechanical testing for a P91 power plant steel, under isothermal, and in-phase and out-of-phase thermo-mechanical, temperature-strain cycle conditions, has been implemented. Using the experimental data, an optimisation procedure has been developed for the accurate determination of the material constants under isothermal conditions, in which the Chaboche model is employed to describe material responses. The material was found to exhibit cyclic softening throughout the full life cycles, which is believed to be related to the evolution of microstructure and the propagation of micro-cracks. The model developed shows good predictive capability of cyclic stress–strain behaviour and cyclic softening.